A Comparative Analysis of Adlerian and Theocentric Philosophies - Briggs, Daniel A (1994)
This research was a comparative historical analysis of Adler's Individual Psychology, Freud's system of psychoanalysis, and Theocentric Psychology. It was assumed that Adlerian constructs are very distinct from Freud's and are greatly influenced by Judaism and Judeo-Christianity. It was further assumed that if these distinctions and influences could be elucidated via historical research, Adlerian Psychology would seem more palatable to Apostolics (an Apostolic is any individual that adheres to the Apostle's fundamental dogma as presented in the book of Acts chapter two and Hebrews chapter six) as well as more compatible with Theocentric Psychology. Some of the various theories, constructs, and paradigms that were explored were personality, holism, creativity and choice, teleology, finalism, phenomenology, social interest, inferiority versus superiority, family systems, lifestyle, normal and abnormal psychology, comparative psychology, social psychology, behavior modification, group psychology, and psychopharmacology. The author validated his assumptions by utilizing the scholary inquiry method of historical research that employs several research tools, e.g., examination of intentional and unintentional documents and producing audio and video recordings of personal interviews. These tools disclosed implicit and explicit statements that aligned with the author's assumptions for the study